2021
DOI: 10.3892/ol.2021.12515
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‑18 and ‑10 may be associated with lymph node metastasis in breast cancer

Abstract: Reports on the expression of interleukin (IL)-10 in breast cancer are rare. The present study investigated the correlation between IL-18 and −10 in breast cancer, and assessed their clinical significance. Breast cancer (n=104) and breast fibroadenoma (n=31) tissues that were surgically removed and pathologically confirmed at Jinan Central Hospital Affiliated to Shandong University (Jinan, China) between November 2016 and January 2019 were collected. The expression of IL-18 and −10 was observed via immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…In addition, IL-18 expression was closely correlated with lymphovascular invasion (LVI) and lymph node metastasis. In fact, previous studies have demonstrated a significant increase in the expression of IL-18 in other tumor types, such as gastric cancer, breast cancer, lung cancer, and renal cell carcinoma [12][13][14]22]. Furthermore, tumor-derived IL-18 displays an important role in triggering the metastasis of those cancers by increasing angiogenesis, facilitating immune escape, and decreasing intercellular adhesion [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, IL-18 expression was closely correlated with lymphovascular invasion (LVI) and lymph node metastasis. In fact, previous studies have demonstrated a significant increase in the expression of IL-18 in other tumor types, such as gastric cancer, breast cancer, lung cancer, and renal cell carcinoma [12][13][14]22]. Furthermore, tumor-derived IL-18 displays an important role in triggering the metastasis of those cancers by increasing angiogenesis, facilitating immune escape, and decreasing intercellular adhesion [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, however, some studies indicate that IL-18 exhibits procancer effects. IL-18 levels are significantly increased a series of neoplasms, such as esophageal, pancreatic, and prostate cancer, and associated with advanced tumor stage and poor prognosis [12][13][14]. Thus, IL-18 is considered to have a double-edged regulatory effect on tumor behavior, which may depend on the neoplastic milieu and/or tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…IL-18 modulates Th1 and Th2 immune responses, as well as the activation of NK cells and macrophages[ 39 ]. It is reported that the IL-18 protein is strongly expressed in human BC and lymph node tissues, and is directly associated with lymph node metastasis in BC[ 40 ]. MYD88 serves a critical function in both innate and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 modulates Th1 and Th2 immune responses, as well as the activation of NK cells and macrophages [33]. It is reported that the IL-18 protein is strongly expressed in human BC and lymph node tissues, and is directly associated with lymph node metastasis in BC [34]. MYD88 serves a critical function in both innate and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%